تفسير الآيات المتعلقة بالضيافة من كتاب "في ظلال القرآن" لسيد قطب : دراسة منهجية - Syed Mohamad Zainudin bin Bichk Koyak (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The study focuses on interpretation of Quranic verses on hospitality according to Tafsir Zilalil ‎Quran (1991), through the elaboration about the methodology that was used by Sayyid Qutb in ‎his book, Zilalil Quran (1991), and extraction of his view about hospitality in Islam. This study ‎elaborates on the good manners and discipline of hospitality that was extracted from a number ‎of stories from Al-Quran. This study also explains certain types of hospitality that have been ‎shown by Sayyid Qutb in his Tafsir. To achieve the research objectives, appropriate research ‎methods were utilized. The inductive method was used through extraction of Quranic verses ‎that relate to hospitality, whether Quranic stories, or certain words that relate to hospitality, and ‎Sayyid Qutb's explanation on each verses. Then, through the analytical method, the verses were ‎studied and analyzed by referring to Tafsir Zilalil Quran. From this method of study, the good ‎manners or adab of hospitality that are in the selected Quranic verses were extracted, and the ‎methodology that was used by Sayyid Qutb in elaborating the verses was extracted. The study ‎primarily shows that hospitality is not just about the host and the guest, it is also about family ‎and community, regardless whether or not people are Muslim or non-Muslim. Hospitality is not ‎just good manners and guidelines. It is the law (shari'ah) stated in Al-Quran and Al-Sunnah. ‎Hospitality is not just for strangers who come to our house, it is also for our family who live ‎with us and our neighbours who communicate with us in our society. The study ends with some ‎recommendations.‎